Striving for Inclusion—A Systematic Review of Long-Term Participation in Strategic Management of Urban Green Spaces - Fors, Hanna; Hagemann, Frederik Aagaard; Sang, Åsa Ode; Randrup, Thomas B. (Frontiers in Sustainable Cities, 2021)
This systematic review contributes to the research field of user participation by suggesting a new holistic approach comprising a cyclic process model for long-term participation in the strategic management of urban green spaces, including analysis, design, and implementation phases, each followed by an evaluation. User participation in urban green spaces is encouraged in international conventions. Such initiatives aim to involve citizens more closely in decisions regarding local spaces, based on the premise that this will create better, more inclusive, and sustainable local environments. However, a social inclusion perspective is largely absent in the growing body of European scientific literature on urban green spaces. Further, user participation processes are often carried out within projects, with uncertainties about which strategic management phase (planning, design, construction, and/or maintenance) to emphasize and about the long-term sustainability of project-based participation. Therefore, the literature was examined for tools for participation with the focus on participation of local users in the strategic management of urban green spaces, and in particular, marginalized groups. A systematic review based on peer-reviewed scientific papers revealed the necessity for adapting participation processes to the known needs of different participant groups, including those of marginalized groups often excluded in the past. Local authorities have several pathways to socially inclusive and long-term participation. These include choosing and employing a suitable participation approach, anchoring repeated project-based participation in existing municipal long-term strategies, continuously supporting participating users and evaluating ongoing participation processes, and employing a mix of participation types and approaches. The “cyclic process model for long-term participation in strategic management of UGS” presented in this paper could guide such efforts.